2006
DOI: 10.1523/jneurosci.4558-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Receptive Field Properties of Neurons in the Early Visual Cortex Revealed by Local Spectral Reverse Correlation

Abstract: We introduce a novel class of white-noise analyses, named local spectral reverse correlation (LSRC), which is capable of revealing various aspects of visual receptive field profiles that were undetectable previously in a single simple measurement. The method is based on spectral analyses in a two-dimensional spatial frequency domain for spatially localized areas within and around their receptive fields. Extracellular single-unit recordings were performed for area 17 and 18 neurons in anesthetized cats. A dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 42 publications
3
62
0
Order By: Relevance
“…Then, optimal orientations and SFs for grating stimuli were measured for both eyes by subspace mapping and/or drifting gratings (Nishimoto et al 2005). The RFs of the cells were also measured using a standard reverse correlation procedure with dense white noise stimuli (Nishimoto et al 2006;Sasaki and Ohzawa 2007) in most cases. The stimulus size was set to be slightly (approximately 10 -30%) larger than the RF size determined by the above reverse correlation procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Then, optimal orientations and SFs for grating stimuli were measured for both eyes by subspace mapping and/or drifting gratings (Nishimoto et al 2005). The RFs of the cells were also measured using a standard reverse correlation procedure with dense white noise stimuli (Nishimoto et al 2006;Sasaki and Ohzawa 2007) in most cases. The stimulus size was set to be slightly (approximately 10 -30%) larger than the RF size determined by the above reverse correlation procedure.…”
Section: Methodsmentioning
confidence: 99%
“…To examine the reliability of estimation of preferred orientation, we asked whether preferred orientation was stable during dichoptic dynamic noise stimulation for each eye. Spike-triggered noise patterns windowed by the actual RF envelope were averaged in the spatial frequency domain separately for each eye to obtain tuning curves for orientation (David et al, 2004;Nishimoto et al, 2006). When the former and latter trials were analyzed separately, the cell presented in Figure 10 A showed consistent preferred orientation between the two time intervals (⌬orientation, 3°; p ϭ 0.34, bootstrap test for the left eye; ⌬ori-entaion, 3°; p ϭ 0.28, bootstrap test for the right eye).…”
Section: Binocular Rfs In 3d Space and Disparity Tunings At Differentmentioning
confidence: 99%
“…An alternative approach, as used in this study, is to stimulate the entire RF but to analyze a limited portion of stimuli that are triggered by spikes (Nishimoto et al, 2006) or to build and verify a model with a bank of spatially localized filters (Wu et al, 2006;Willmore et al, 2010). Although the latter strategy is computationally demanding, it requires a small number of physiological experiments in the end because it allows one to customize stimuli minimally during experiments and to test various models or hypotheses during data analysis.…”
mentioning
confidence: 99%
“…With these techniques, spike-triggered stimuli are first converted to their spectra in the spatial frequency domain by the Fourier transform, and then they are averaged in the frequency domain separately for different phases (David et al 2004) or without regard to phase (Nishimoto et al 2006;Ringach et al 1997). Spectral representation potentially enables suppressive responses, such as suppression at low spatial frequency and cross-orientation suppression, to be dissociated from excitatory responses Nishimoto et al 2006;. These suppressive responses are masked by excitatory responses in second-order interaction analysis because they are usually overlapped in the space domain.…”
Section: Relationship To Other Studies On Internal Organizations Of Cmentioning
confidence: 99%